2012
DOI: 10.1103/physrevd.86.103532
|View full text |Cite
|
Sign up to set email alerts
|

Cosmological dynamics of a nonminimally coupled scalar field system and its late time cosmic relevance

Abstract: We investigate the cosmological dynamics of non-minimally coupled scalar field system described by F (φ)R coupling with F (φ) = 1 − ξφ N R(N ≥ 2) and the field potential, V (φ) = V0φ n . We use a generic set of dynamical variables to bring out new asymptotic regimes of the underlying dynamics. However, our dynamical variables miss the most important fixed point− the de Sitter solution. We make use of the original form of system of equations to investigate the issues related to this important solution. In parti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
95
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 105 publications
(98 citation statements)
references
References 55 publications
3
95
0
Order By: Relevance
“…Using the analysis of [19], it is possible to show that for the case of ξ < 0 (the only case we consider in the present paper) the form of phase diagrams does not depend on ξ and depends only upon relations between power indexes of the coupling function and the scalar field monomial potential. This allows us to characterize completely the global feature of cosmological dynamics in the model in question using a limiting number of phase portraits.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Using the analysis of [19], it is possible to show that for the case of ξ < 0 (the only case we consider in the present paper) the form of phase diagrams does not depend on ξ and depends only upon relations between power indexes of the coupling function and the scalar field monomial potential. This allows us to characterize completely the global feature of cosmological dynamics in the model in question using a limiting number of phase portraits.…”
Section: Introductionmentioning
confidence: 99%
“…The models with the Ricci scalar multiplied by a function of the scalar field are being intensively studied in cosmology [7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22] (see also [23,24,25] and references therein). Induced gravity models, wherein the curvature arises as a quantum effect [26], and models, where both the Hilbert-Einstein term and the scalar field squared multiplied by the scalar curvature are present, have been applied to quantum cosmology [27] and are being intensively studied in the inflationary cosmology [7,8,9,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2(a) and in the j − s plane in Fig. 2(b) in the range −1 ≤ q < 1 by considering the mean values of the model parameters given in Table 3 from observations. For comparison, we include also some alternatives to the ΛCDM model such as the Galileon, Chaplygin Gas and DGP models (for these models see [63] and references therein) in the figures. The arrows on the curves show the direction of evolution and the dots on the curves represent the present values of the corresponding {q, j} and {j, s} pairs while the black dots show the matter dominated phases of the models.…”
Section: Observational Constraints On Hel Cosmology From H(z)+sn Ia Datamentioning
confidence: 99%
“…The nonminimal derivative coupling leads to cosmological models with rich phenomenology, such as solutions containing a Big Bang, expanding Universes with no beginning, cosmological bounces, eternally contracting Universes, a Big Crunch, and a Big Rip avoidance [33,[36][37][38][39][40][41][42]. In particular, it was shown that one is able to explain in a unique manner both a quasi-de Sitter phase and an exit from it without any fine-tuned potential [32].…”
Section: Introductionmentioning
confidence: 99%